What are over-the-road truckers paid for? Evidence from an exogenous regulatory change on the role of social comparisons and work organization in wage determination - Stephen V. Burks; Frederick Guy (Institute for the Study of Labor (IZA), 2012)
Using evidence from recent work on truckers and disaggregated older data prior researchers did not have, we revisit a classic topic and find some new answers. We focus on differentials in average annual earnings at the firm level among mileage-paid over-the-road tractor-trailer drivers (road drivers) employed by US for-hire trucking companies, before and after economic deregulation. Road driver output is individualized, and pay is on the basis of a piece rate (mileage). However, road drivers work under two distinct logistical systems - less-than-truckload [LTL], and truckload [TL] - associated with two different forms of work organization. We find that - contrary to the predictions of Rose (1987) - not only are road drivers for LTL companies paid more than those for TL companies, but in LTL the union earnings premium was maintained following deregulation and union coverage fell slowly, while in TL both the union differential and union coverage fell sharply. We review relevant theoretical explanations: payment for cognitive abilities or non-pecuniary disamenities; standard efficiency wage models based on independent utilities; sharing of product market rents; equity concerns resulting from social comparisons between employee groups; and differences in work organization as a source of union rents or quasi-rents. Only equity concerns, for the LTL earnings differential, and quasi rents (but not a union threat effect, contrary to Henrickson and Wilson (2008)), for union coverage and premium in LTL, are consistent with our empirical results. Both earnings differentials are based on differences in work organization, rather than differences in the workers or the work itself.
urn:nbn:de:101:1-201206146507
Keywords: J31; J42; L92; 330; fair wage; equity; compensating differential; cognitive ability; quasi-rent; rent-sharing; work organization; trucking; trucker; less-than-truckload (LTL); truckload (TL); regulation; deregulation; union premium; Verkehrsberufe; Güterkraftverkehrsgewerbe; Deregulierung; Lohnstruktur; Lohnbildung; Arbeitsorganisation; Gewerkschaftsmitgliedschaft; USA